Comparative genomic analyses reveal broad diversity in botulinum-toxin-producing Clostridia. (December 2016) - Williamson, Charles; Sahl, Jason; Smith, Theresa; Xie, Gary; Foley, Brian; Smith, Leonard; Fernández, Rafael; Lindström, Miia; Korkeala, Hannu; Keim, Paul; Foster, Jeffrey; Hill, Karen
Abstract Background Clostridium botulinum is a diverse group of bacteria characterized by the production of botulinum neurotoxin. Botulinum neurotoxins are classified into serotypes (BoNT/A–G), which are produced by six species/Groups ofClostridia, but the genetic background of the bacteria remains poorly understood. The purpose of this study was to use comparative genomics to provide insights into the genetic diversity and evolutionary history of bacteria that produce the potent botulinum neurotoxin. Results Comparative genomic analyses of over 170Clostridia genomes, including our draft genome assemblies for 59 newly sequencedClostridia strains from six continents and publicly available genomic data, provided in-depth insights into the diversity and distribution of BoNT-producing bacteria. These newly sequenced strains included Group I and II strains that express BoNT/A, /B, /E, or/F as well as bivalent strains. BoNT-producingClostridia and closely relatedClostridia species were delineated with a variety of methods including 16S rRNA gene, concatenated marker genes, core genome and concatenated multi-locus sequencing typing (MLST) gene phylogenies that related whole genome sequenced strains to publicly available strains and sequence types. These analyses illustrated the phylogenetic diversity in each Group and the diversity of genomic backgrounds that express the same toxin type or subtype. Comparisons of the botulinum neurotoxin genes did not identify novel toxin types or variants. Conclusions This study represents one of the most comprehensive analyses of whole genome sequence data for Group I and II BoNT-producing strains. Read data and draft genome assemblies generated for 59 isolates will be a resource to the research community. Core genome phylogenies proved to be a powerful tool for differentiating BoNT-producing strains and can provide a framework for the study of these bacteria. Comparative genomic analyses ofClostridia species illustrate the diversity of botulinum-neurotoxin-producing strains and the plasticity of the genomic backgrounds in whichbont genes are found.